Device for Current Test Pulse Development Through a Diode in a Direct Direction - Bespalov, Nikolay; Goryachkin, Yury (International Journal of Engineering and Technology, 2018)
The article is devoted to the development of a device that allows to generate control current pulses to determine the current-voltage characteristic of diodes in the forward direction. To implement the device, we use NI Digital Electronics FPGA Board, which includes FPGA XC3S500E Xilinx Spartan-3E FPGA and the Linear Technology LTC2624 chip, containing four 12-bit DACs. We consider the creation of a software module via VHDL language that generates 12-bit digital code to create rectangular voltage control pulses with a successively increasing amplitude and transmitted via SPI interface as the part of 32-bit data transfer protocol, using Xilinx WebPACK ISE software.Â